Investigating Elementary School Teacher Gestures in Mathematics Teaching and Learning - Nasrun, Nasrun; Syawahid, M.; Akib, Irwan (Universitas Muhammadiyah Mataram, 2023)
Gestures was an important in mathematics teaching and learning because it can increase student’s cognitive load. however, many teachers pay little attention to gestures in carrying out learning in class. This study aims to describe and compare the gesture of primary school teacher in mathematics teaching and learning. Qualitative of case study used in this study. Two teachers in “Islam Athirah” of elementary schools consist of one senior teacher and one prospective teacher as research subjects. Data was collected through audiovisual material and interview. The teachers were observed and recorded when performing mathematics teaching and learning. Interview were conducted with ten selected students to find out feedback from learning activity. The finding showed that pointing gesture was frequently used in mathematics teaching and learning. Furthermore, senior teacher better in performing gesture than pre-service teacher. Senior teacher has an excellence in pointing and writing gesture, while pre-service teacher has an excellence in performing representing gesture.